ANALISA RESISTIVITAS KAWAT PENGHANTAR DITINJAU DARI METODE JEMBATAN WHEATSTONE DAN METODE HUKUM OHM PADA MODUL PRAKTIKUM FISIKA - Tatik Juwariyah; Yuhani Djaja (Bina Teknika, 2016)
The analysis of the resistivity of a wire based on the Wheatstone bridge method and the Ohm law method in physics experiment module has been done. The analysis of the resistivity of a wire was done in a physics laboratory at UPNVJ engineering faculty. This topic was studied because there has been no experiment in the themed of electricity in the physics experiment module at the faculty of engineering UPNVJ. The most popular method applied to obtain wire resistivity value is the Ohm law method. In order to enlarge the understanding of the electricity concept, this research needed other method that can be used to find out the wire resistivity namely the Wheatstone Bridge method. This research aimed to obtain the resistivity value of Nichrome wire from two different methods. The methods were the Ohm law method and the Wheatstone bridge method. In Ohm law method, the wire length was subsequent varied. Then, the electric voltage value and an electric current were recorded. While in the Wheatstone bridge method, it was used circuit bridge. The value of the variable resistor was varied and the segment length metal plate was measured. The data were processed in order to obtain the Nichrome wire resistivity values by linear regression method. From Ohm law method and the Wheatstone bridge method were respectively obtained the value of Nichrome wire was ρ±Δρ=(2,875±0,005)x10-6 Ωm and ρ±Δρ=(5,00±0,25)x10-6 Ωm. The results of the two methods are match with the value of the standard of the Nichrome wire is ρ=1,0x10-6 Ωm. By using the two methods, it was expected that the students’ understanding of the electricity concept was increasingly widespread.